2019
DOI: 10.22616/foodbalt.2019.014
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of organically grown apple cultivars for special diet puree production

Abstract: The aim of this research was to evaluate organically grown Latvian extensive apple cultivars for production of puree for special diets with high content of bioactive compounds. Five organically grown extensive cultivars were selected for evaluation within the project: 'Antonovka', 'Filippa', 'Nicnera Zemenu', 'Rudens Svitrotais', 'Sipolins'. All these apple cultivars were evaluated fresh and after processing into puree. The content of soluble solids, titratable acids, vitamin C, total carotenes, total phenols,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…The main factors influencing antioxidant activity are phenolic compounds [29]. Based on the results obtained, it can be concluded that there is a correlation between the total content of polyphenols and the antioxidant activity, a conclusion also reached by Loncaric (2014), Park et al (2015) and Kampuse et al (2019) [27,48,62]. In the case of purees, with the decrease in the total content of polyphenols, the antioxidant activity also decreased; similar results were obtained by Loncaric et al (2014) [27].…”
Section: Antioxidant Capacitysupporting
confidence: 59%
See 2 more Smart Citations
“…The main factors influencing antioxidant activity are phenolic compounds [29]. Based on the results obtained, it can be concluded that there is a correlation between the total content of polyphenols and the antioxidant activity, a conclusion also reached by Loncaric (2014), Park et al (2015) and Kampuse et al (2019) [27,48,62]. In the case of purees, with the decrease in the total content of polyphenols, the antioxidant activity also decreased; similar results were obtained by Loncaric et al (2014) [27].…”
Section: Antioxidant Capacitysupporting
confidence: 59%
“…In the case of the raw mash, respectively the cooked mash, a decrease in the content of polyphenols was determined during the storage period. In the cooked mash, a higher content of polyphenols was obtained by up to 51% compared to the raw mash, this fact being due to the change in the concentration of the sample during the heat treatment, with similar results being obtained by Park et al (2015) and Kampuse et al (2019) [43,48,62]. The significant decrease in the total content of polyphenols in the cooked puree, compared to that of the raw puree, is due to the catalysis of the oxidation of phenolic compounds by polyphenoloxidase.…”
Section: Total Phenolic Contentmentioning
confidence: 56%
See 1 more Smart Citation